Revisiting Hayek's political economy - Boettke, Peter J.; Storr, Virgil Henry, 1975- (Emerald, 2016)
Advances in Austrian Economics is a research annual whose editorial policy is to publish original research articles on Austrian economics. Each volume attempts to apply the insights of Austrian economics and related approaches to topics that are of current interest in economics and cognate disciplines. Volume 21 exemplifies this focus by highlighting key research from the Austrian tradition of economics with other research traditions in economics and related areas.
Keywords: Hayek, Friedrich A. von -- (Friedrich August), -- 1899-1992.; Economics -- History -- 20th century.; Austrian school of economics -- History.; elektronické knihy; electronic books